A comparative evaluation of microleakage between resin-modified glass ionomer, flowable composite, and cention-N in Class V restorations: A confocal laser scanning microscope study - Krishnan Venugopal; L Krishnaprasad; V P Prabath Singh; Arjun B Ravi; Kaushik Haridas; Drisya Soman (Wolters Kluwer Medknow Publications, 2021)
Background: Microleakage is a concern while restoring cervical lesions. Many products have attempted to minimize the interfacial gap between the tooth and restoration, the main pathway of microleakage. Aims and Objective: To compare and evaluate the microleakage in Class V cavity restored with nanohybrid flowable composite, Resin modified Glass Ionomer and Cention N. Method: Class V cavities were prepared on mandibular premolars on buccal surface with their occlusal margin placed in enamel and the gingival margin in dentin. The teeth were randomly assigned to three groups of 20 teeth each and restored with Flowable composite , Resin Modified GIC and Cention N. Samples were immersed in 0.5% Rhodamine dye, sectioned and microleakage measured using Confocal Laser Scanning Microscopy. Statistical analysis was done using Oneway ANOVA Bonferroni's test and Kruskal Waliis test. Results: The average depth of penetration of dye and scoring of depth were noted. On comparing dye penetration values between groups, RMGIC is compared with Flowable composite and Cention N, statistically significant result was obtained suggesting lesser dye penetration in RMGIC group (P < 0.001) where other comparison did not. Conclusion: RMGIC showed significantly less microleakage compared to the other two restorative materials used in the study and enamel margin of all restorations showed lesser microleakage than dentin margin.